2012
DOI: 10.1007/s12016-012-8300-8
|View full text |Cite
|
Sign up to set email alerts
|

Allergic and Immunologic Reactions to Food Additives

Abstract: For centuries, food additives have been used for flavouring, colouring and extension of the useful shelf life of food, as well as the promotion of food safety. During the last 20 years, the studies implicating the additives contained in foods and medicine as a causative factor of allergic reactions have been proliferated considerably. In this review, we aimed to overview all of the food additives which were approved to consume in EU and find out how common and serious allergic reactions come into existence fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 195 publications
0
63
0
1
Order By: Relevance
“…The extensive use of synthetic food additives are suspected for inducing negative impact to human health (Gultekin and Doguc, 2013;Metcalfe et al, 2009). According to Gultekin and Doguc (2013) all food additives are potential hidden allergens, and every human being is inevitably exposed to them every day.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extensive use of synthetic food additives are suspected for inducing negative impact to human health (Gultekin and Doguc, 2013;Metcalfe et al, 2009). According to Gultekin and Doguc (2013) all food additives are potential hidden allergens, and every human being is inevitably exposed to them every day.…”
Section: Introductionmentioning
confidence: 99%
“…According to Gultekin and Doguc (2013) all food additives are potential hidden allergens, and every human being is inevitably exposed to them every day. Effects of food additives can be immediate or longterm if the consumption is constant (Gultekin and Doguc, 2013). Β-carotene is widely used in the food, cosmetics and pharmaceutical industry as coloring, antioxidant and anti-inflammatory agent.…”
Section: Introductionmentioning
confidence: 99%
“…The same can result in urticaria in some patients with hypersensitivity, and anaphylaxis, urticaria and angioedema. 11,27 In a case study with a 47 year old woman that had asthma, allergic rhinitis and syndrome of oral allergy, it was concluded that these adverse effects emerged after patient contact with the dye carmine on 3 products -yogurt, red tortellini and makeup -and also ingested drug containing the dye, which was later replaced with one that had not carmine in its composition. 28 The dye Bordeaux S, also known as amaranth, is part of a group of dyes in their degradation can release toxic compounds, indicating carcinogenic action.…”
Section: Resultsmentioning
confidence: 99%
“…F. Gultekin, D. K. Dogue 2012 m. paskelbė straipsnį, kuriame apžvelgė alergines reakcijas į maisto priedus. Tačiau šios reakcijos dažniausiai buvo diagnozuotos dirbantiems maisto pramonėje asmenims, kurie turėjo nuolatinį kontaktą su pramonėje naudojamais maisto priedais [36].…”
Section: Padidėjusio Jautrumo Maisto Produktams Ir Priedams Klasifikaunclassified